Dynamic analysis of concentrated solar supercritical CO2-based power generation closed-loop cycle. (25th January 2016) - Osorio, Julian D.; Hovsapian, Rob; Ordonez, Juan C.
Highlights: Dynamic modeling of a central receiver sCO2 Brayton CSP system is presented. Effects of design and operating parameters on the system performance are studied. Seasonal conditions have a strong impact in the system efficiency and power output. Efficiencies found are comparable with efficiencies of high performance PV panels. Graphical Abstract: Abstract: In this study, the dynamic behavior of a concentrated solar power (CSP) supercritical CO2 cycle is studied under different seasonal conditions. The system analyzed is composed of a central receiver, hot and cold thermal energy storage units, a heat exchanger, a recuperator, and multi-stage compression–expansion subsystems with intercoolers and reheaters between compressors and turbines respectively. Energy models for each component of the system are developed in order to optimize operating and design parameters such as mass flow rate, intermediate pressures and the effective area of the recuperator to lead to maximum efficiency. The results show that the parametric optimization leads the system to a process efficiency of about 21% and a maximum power output around 1.6 MW. The thermal energy storage allows the system to operate for several hours after sunset. This operating time is approximately increased from 220 to 480 minutes after optimization. The hot and cold thermal energy storage also lessen the temperature fluctuations by providing smooth changes of temperatures at the turbine and compressor inlets. The results obtained in this paper indicate that concentrated solar systems using supercritical CO2 could be a viable alternative to satisfying energy needs in desert areas with scarce water and fossil fuel resources.